2014
DOI: 10.1590/s0036-46652014000200003
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF Bifidobacterium animalis ON MICE INFECTED WITH Strongyloides venezuelensis

Abstract: The administration of viable Bifidobacterium animalis was tested to induce resistance against Strongyloides venezuelensis infection in mice. Effects on parasite burden, worm length, egg output, and intestinal mucosal histology were evaluated. The oral administration of B. animalis, strain 04450B, starting 14 days before the inoculation of nematode larvae significantly decreased the worm burden and egg output. In probiotic treated animals, the percent reduction of adult worms in the intestine was of 33% and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
(46 reference statements)
1
16
0
Order By: Relevance
“…Indeed, previous investigations in cattle and mice have reported that host genes encoding for antimicrobial proteins are up-regulated in the mucosae of animals resistant to helminth infection ( D'Elia et al, 2009 , Li et al, 2015 ). In addition, dietary supplementation with both pro- ( Bautista-Garfias et al, 1999 , Bautista-Garfias et al, 2001 , Martinez-Gomez et al, 2009 , Martinez-Gomez et al, 2011 , Oliveira-Sequeira et al, 2014 , El Temsahy et al, 2015 ) and pre-biotics ( Petkevicius et al, 2003 , Petkevicius et al, 2004 , Petkevicius et al, 2007 , Thomsen et al, 2005 , Jensen et al, 2011 ), has led to significant reductions in worm burdens in murine and swine helminth infection models, thus indicating that alterations of the gut bacterial flora may bias host immune responses against parasites. Further characterisation of equine host mucosal responses and GI microbiota, in the presence or absence of helminth infection and accompanied by total enumeration of infecting parasites, is a key area of future research, as it may lead to the identification of microbial factors linked to host susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous investigations in cattle and mice have reported that host genes encoding for antimicrobial proteins are up-regulated in the mucosae of animals resistant to helminth infection ( D'Elia et al, 2009 , Li et al, 2015 ). In addition, dietary supplementation with both pro- ( Bautista-Garfias et al, 1999 , Bautista-Garfias et al, 2001 , Martinez-Gomez et al, 2009 , Martinez-Gomez et al, 2011 , Oliveira-Sequeira et al, 2014 , El Temsahy et al, 2015 ) and pre-biotics ( Petkevicius et al, 2003 , Petkevicius et al, 2004 , Petkevicius et al, 2007 , Thomsen et al, 2005 , Jensen et al, 2011 ), has led to significant reductions in worm burdens in murine and swine helminth infection models, thus indicating that alterations of the gut bacterial flora may bias host immune responses against parasites. Further characterisation of equine host mucosal responses and GI microbiota, in the presence or absence of helminth infection and accompanied by total enumeration of infecting parasites, is a key area of future research, as it may lead to the identification of microbial factors linked to host susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics, including species of Lactobacillus and Bifidobacterium (Butel, 2014 ), are thought to protect against infection by competing with pathogens for space and resources, modulating the host immune system, and producing antimicrobial peptides (Corr et al, 2009 ). Although studies investigating the effects of probiotics on helminth infections have yielded conflicting results, with studies showing that probiotics can reduce helminth burdens (Stefanski and Przyjalkowski, 1965 , 1966 ; Bautista-Garfias et al, 1999 , 2001 ; Santos et al, 2004 ; Basualdo et al, 2007 ; Martínez-Gómez et al, 2009 , 2011 ; Chiodo et al, 2010 ; Oliveira-Sequeira et al, 2014 ), increase susceptibility to helminths (Dea-Ayuela et al, 2008 ; Reynolds et al, 2014 ), or have no effect on helminth burden (de Waard et al, 2001 ; Verdú et al, 2004 ), the majority of published studies have found a decrease in helminth burdens with probiotic administration. This suggests that certain probiotic species may help protect against helminth infection, though the underlying mechanisms remain unclear.…”
Section: Applications Of Understanding Parasite-microbiota Interactiomentioning
confidence: 99%
“…Moreover, an increase in leukocyte and lymphocyte counts was reported [ 79 ], suggesting the immune activation effects of probiotics. On the other hand, Bifidobacterium animalis strain 04450B at dose of 2 × 10 9 CFU revealed a much lower response with 33% reduction of adult worms and 21% reduction of egg production in Strongyloides venezuelensis infected mice [ 80 ].…”
Section: Trends Of Probiotics Against Helminth Zoonosismentioning
confidence: 99%